The absolute percent deviation of IGHV mutation rather than a 98% cut‐off predicts survival of chronic lymphocytic leukaemia patients treated with fludarabine, cyclophosphamide and rituximab. (21st November 2017) - Jain, Preetesh; Nogueras González, Graciela M.; Kanagal‐Shamanna, Rashmi; Rozovski, Uri; Sarwari, Nawid; Tam, Constantine; Wierda, William G.; Thompson, Philip A.; Jain, Nitin; Luthra, Rajyalakshmi; Quesada, Andres; Sanchez‐Petitto, Gabriela; et al.
Summary: The degree of somatic hypermutation, determined as percent deviation of immunoglobulin heavy chain gene variable region sequence from the germline ( IGHV %), is an important prognostic factor in chronic lymphocytic leukaemia (CLL). Currently, a cut‐off of 2% deviation or 98% sequence identity to germline in IGHV sequence is routinely used to dichotomize CLL patients into mutated and unmutated groups. Because dissimilar IGHV % cut‐offs of 1–5% were identified in different studies, we wondered whether no cut‐off should be applied and IGHV % treated as a continuous variable. We analysed the significance of IGHV % in 203 CLL patients enrolled on the original frontline fludarabine, cyclophosphamide and rituximab (FCR) trial with a median of 10 years follow‐up. Using the Cox Proportional Hazard model, IGHV % was identified as a continuous variable that is significantly associated with progression‐free (PFS) and overall survival (OS) ( P < 0·001). Furthermore, we validated this finding in 323 patients treated with FCR off‐protocol and in the total cohort ( n = 535). Multivariate analysis revealed a continuous trend. Higher IGHV % levels were incrementally associated with favorable PFS and OS in both FCR‐treated cohorts ( P < 0·001, both cohorts). Taken together, our data suggest that IGHV % is a continuous variable in CLL patients treated with FCR.